Inferior Oblique Entrapment After Orbital Fracture With Transection and Repair. Issue 3 (September 2020) - Tooley, Andrea A.; Levine, Benjamin; Godfrey, Kyle J.; Lisman, Richard D.; Tran, Ann Q.; Sherman, John E.
Extraocular muscle (EOM) entrapment with resulting reduction in motility and diplopia is a known complication of orbital fractures. Less commonly, transection of the EOMs due to trauma, iatrogenic injury, or intentional myotomy may lead to persistent diplopia. The inferior oblique (IO) is often encountered during orbital surgery along the medial wall and floor, and may be disinserted to aid in visualization. The authors present a case of IO entrapment which occurred during zygomaticomaxillary fracture reduction. Intraoperatively, an IO transection was performed and the muscle was reattached within the orbit. Postoperatively, the patient did not develop diplopia or motility disruption. This technique may provide a useful solution to an unusual problem during orbital fracture repair.